Demography and Income in the 21st Century: A Long-Run Perspective - Steven Brakman; Tristan Kohl; Charles van Marrewijk (CESifo GmbH, 2024)
Population forecasts indicate that the world is facing massive demographic changes during the 21st century. This does not only involve the development of the total global population, but (more importantly) will also affect the population and age distribution across countries in a fundamental way. In this paper we focus on the income consequences of these changes for the global income distribution. Key in this respect are changes in the so-called demographic dividend associated with the share of the working-age population in the total population. We link the predicted long-run changes of the demographic dividend to income projections. Our findings are as follows. First, show that historically the impact of demography on economic growth indicates that a one per cent higher demographic dividend results in about 0.22 percentage points higher growth rate. Second, we use UN population projections on population size and the associated age-distribution to predict income changes for the remainder of this century. Third, we illustrate how the center of income gravity shifts from advanced economies, like Europe and North America, towards developing and emerging economies, like South Asia and Africa. This potentially has consequences for the current global economic powers, that will see their influence on world affairs decline.
Keywords: F43; J11; 330; demography; income